2011
DOI: 10.1038/cr.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Imaging superoxide flash and metabolism-coupled mitochondrial permeability transition in living animals

Abstract: The mitochondrion is essential for energy metabolism and production of reactive oxygen species (ROS). In intact cells, respiratory mitochondria exhibit spontaneous "superoxide flashes", the quantal ROS-producing events consequential to transient mitochondrial permeability transition (tMPT). Here we perform the first in vivo imaging of mitochondrial superoxide flashes and tMPT activity in living mice expressing the superoxide biosensor mt-cpYFP, and demonstrate their coupling to whole-body glucose metabolism. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
157
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(166 citation statements)
references
References 34 publications
(40 reference statements)
9
157
0
Order By: Relevance
“…Mitochondria in skeletal muscle cells exhibited spontaneous SO flashes that occurred throughout the mitochondrial network of individual cells. SO flashes occurred asynchronously in individual mitochondria distributed along axons of the sciatic nerve and, interestingly, SO flashes occurred only in mitochondria that were stationary and not in mitochondria that were being npg actively transported along the axons [9]. Additional experiments in the new study showed that, as was the case in cell culture, the SO flashes are associated with and require the opening of mPTP.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…Mitochondria in skeletal muscle cells exhibited spontaneous SO flashes that occurred throughout the mitochondrial network of individual cells. SO flashes occurred asynchronously in individual mitochondria distributed along axons of the sciatic nerve and, interestingly, SO flashes occurred only in mitochondria that were stationary and not in mitochondria that were being npg actively transported along the axons [9]. Additional experiments in the new study showed that, as was the case in cell culture, the SO flashes are associated with and require the opening of mPTP.…”
mentioning
confidence: 71%
“…Fourth, how is the frequency of the SO flashes modified by physiological signaling and in pathological settings? Fang et al [9] found that when mice were administered either glucose or insulin the frequency of the mitochondrial SO flashes increased. Glucose might increase SO flash frequency by providing more substrate for oxidative phosphorylation, and insulin might act by increasing glucose transport.…”
mentioning
confidence: 99%
See 3 more Smart Citations